Recent Students’ Motivation Toward Learning English After the COVID-19 Post-Pandemic - Firmansyah, Bihan; Hamamah, Hamamah; Emaliana, Ive (JOLLT Journal of Languages and Language Teaching, 2023)
The COVID-19 pandemic has compelled EFL teachers to adapt their instruction online. Evidence shows how protracted school closures affect students’ ability to learn EFL. The development of techniques to aid students in making up for lost learning would require this knowledge for EFL learning. For this reason, it is necessary to know in greater detail students’ motivation to learn EFL in the post-pandemic era. It is vital to have a clear plan for individualized diagnoses and to put remedial programs into place. 100 senior high school students from a private school participated. Data for this study were gathered using an online self-reported questionnaire measuring intrinsic and extrinsic motivation which can encourage studentsâ€™ EFL learning. The results of the study showed a variety of learnersâ€™ internal and external factors of motivation such as studentsâ€˜ desire to learn a language to improve their skills, learn about diverse cultures, beliefs, and viewpoints, and simply to pass their exam. Thus,Â acting as either pulling or dragging forces of learning English. Besides the limitations, these research results would impact teachersâ€™ teaching strategies, materials, and media selections to reduce studentsâ€™ learning loss.